Studi Fenomenologi: Audit Investigasi dalam Pengungkapan Fraud - Iqbal, Mohammad; Utami, Helianti (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2024)
Purpose: This research aims to provide an in-depth understanding of investigative audits in uncovering fraud using a phenomenological approach. Method: This study involves six auditors from 3 KAPs in Malang City. Research data was obtained through semi-structured interviews. Interview data was analyzed by taking the essence of noema and noesis to get meaning. Results: Not all auditors use the latest investigative audit standards when conducting investigative audits. Understanding investigative audit standards, accounting, and legal is needed to support competence, apart from experience and certification. The complexity of audit procedures in analyzing data is an obstacle auditors face. In addition, the threat of intimidation felt by auditors can disrupt the audit process. The availability of data and collaboration with related parties supports the success of an investigative audit. Implications: Auditors must participate in continuous professional training in investigative audits to improve their competence. Apart from that, cooperation between various parties is needed to provide auditors with audit data and a sense of security. Novelty: This research contributes to the investigative audit literature using a qualitative phenomenological approach, which is still rarely found. The phenomenological approach provides an in-depth understanding of investigative audits from the perspective of its auditors.